2007
DOI: 10.1161/01.atv.0000255310.47940.3b
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Quantification of Atherosclerosis in an Elderly Population Assessed by Whole-Body Magnetic Resonance Angiography

Abstract: Objective-The principal aim of the present study was to explore the feasibility of using whole-body magnetic resonance angiography to assess atherosclerosis in different vascular territories in a cohort of elderly. Methods and Results-Three hundred six 70-year-old subjects (145 women, 161 men) recruited from a population-based cohort study (Prospective Investigation of the Vasculature in Uppsala Seniors, ie, the PIVUS study) underwent 1.5-T whole-body magnetic resonance angiography with gadodiamide. The arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…One radiologist with 3 years' experience evaluated all WBMRA examinations blinded to other information. The intra-and inter-observer agreement has previously been reported using this method, ranging from good to excellent with kappa values of 0.73 and 0.83, respectively [3].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One radiologist with 3 years' experience evaluated all WBMRA examinations blinded to other information. The intra-and inter-observer agreement has previously been reported using this method, ranging from good to excellent with kappa values of 0.73 and 0.83, respectively [3].…”
Section: Discussionmentioning
confidence: 71%
“…intravascular US of the coronary vessels or digital subtraction angiography (DSA) of vessels of a limited region, the availability of whole-body MRA (WBMRA) provides a opportunity to simultaneously estimate the total amount of stenotic vascular disease in different vascular territories as well as the total body atherosclerotic burden with the exclusion of the coronary and intracranial vessels. The results for the vessel segments of the WBMRA examinations using this population have been reported previously [3]. In a study based on patients with suspected coronary disease, a atherosclerosis index as revealed by WBMRA were related to coronary artery calcium scoring (CACS) [4].…”
Section: Introductionmentioning
confidence: 96%
“…The prevalence of atherosclerotic changes in different vessel territories in this cohort have been reported previously. 9 Exclusion criteria for the WB-MRA examination were a pacemaker, valvular prostheses, intracranial clips, and claustrophobia. Of the included participants, 306 could complete the WBMRA examination.…”
Section: Methodsmentioning
confidence: 99%
“…16,17 As a second step, we studied the prospective association between PTH and the risk of peripheral and large vessel atherosclerotic disease in an independent community-based sample of elderly men.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 99%